Effective targeting of colorectal cancer cells using TORC1/2 kinase inhibitors in vitro and in vivo. (February 2016) - Zhang, Jie; Jiang, Wen; Liu, Wei; Wu, Juan-Juan; Song, Lei; Cheng, Ji-Xian; Yao, Ming; Yang, Li-Ping; Yao, Deng-Fu
Aim: We investigated the effects of TORC1/2 kinase inhibitors on colorectal cancer (CRC) cell lines.Materials & methods: Using selective TORC1/2 inhibitors, rapamycin and PP242, we assessed their effect on the growth of CRC cells in vitro and tumor growth in vivo .Results: Rapamycin and PP242 inhibit proliferation and induce apoptosis of CRC cells. They also enhance proapoptotic effect of conventional chemo drug doxorubicin in CRC cells in vitro . When combined with doxorubicin, rapamycin and PP242 almost completely inhibit tumor growth in vivo . Rapamycin and PP242 inhibit phosphorylation of Akt, ribosomal S6 kinase, 4EBP1 and mTOR.Conclusion: Our study suggests rapamycin and PP242 may be a useful therapeutic agent and inhibiting mTOR signaling pathway represents a new targeted therapy for CRC.